Contribution of the V.P. Gorychkin Gold Medal Laureates to the Agroengineering Science Development - Yu. S. Tsench (Сельскохозяйственные машины и технологии, 2023)
In the practice of the Russian Academy of Sciences, it is established in the main scientific areas to periodically award gold medals named after outstanding domestic scientists of agrarian science on a competitive basis. According to the profile of agroengineering science, such a medal is dedicated to the founder of the doctrine of agricultural machines, Academician Vasily Prokhorovich Goryachkin. (Research purpose). To carry out a survey of the agricultural engineering science from the historical perspective, summarize its scientific achievements and recreate a holistic picture of the scientific heritage left by the followers of V.P. Goryachkin, who are known in the agricultural engineering science as laureates of the Gold Medal of the Russian Academy of Sciences named after V.P. Goryachkin. (Materials and methods). The article traces the development of scientific ideas of V.P. Goryachkin in the works of renowned domestic scientists in the agricultural engineering sciences. (Results and discussion). The article presents a holistic picture of the scientific achievements from 1971 to 2022 made by the followers of V.P. Goryachkin, those who were awarded the Gold Medal named after him. For more than 50 years, fifteen outstanding scientists have been awarded the Gold Medal of the Russian Academy of Sciences named after V.P. Goryachkin, in particular: V.A. Zheligovsky (1971), I.I. Artobolevsky (1974), P.I. Vasilenko (1977), I.A. Budzko (1986), G.E. Listopad (1989), N.I. Klenin (1992), N.V. Krasnoshchekov (1995), V.I. Chernoivanov (1998), I.P. Ksenevich (2001), L.P. Kormanovsky (2004), V.M. Kryazhkov (2008), V.I. Syrovatke (2011), E.V. Zhalnin (2014), A.I. Zavrazhnov (2018), M.N. Erokhin (2022). (Conclusions) Outstanding Russian scientists, laureates of the Academician V.P. Goryachkin gold medal made a huge contribution to the further development of agroengineering science and education, the formation of fundamental scientific schools, the development of theoretical and practical foundations for the creation of innovative technologies, systems and machine complexes.